La linguistique et le langage animal. Résistances, décentrements, propositions - Marie-Anne Paveau; Catherine Ruchon (Itinéraires)
While many disciplines are interested in the production of meanings by animals, language sciences resist and camp on anthropocentric positions that isolate them in the humanities and social sciences at the international level. In this article, we try to understand what blocks linguists from taking into account only human language and to identify the locks that prevent them from taking into account non-human elements, whereas ethologists, philosophers, cognitivists, anthropologists, sociologists or psychologists ask the question of animal language. We first examine the forms of this resistance in linguistics by studying three specific discourses: an anthropocentric professional doxa, the prevalence of a negative axiological conception of anthropomorphism and the scientific construction of this resistance, based on the notions of language articulation and symbolisation. We then identify three locks to explain this lack of consideration of the non-human: the ideological lock of anthropocentrism or human superiority; an epistemological lock maintaining logocentrism as an analytical framework for linguistics; a psycho-professional lock, close to cognitive dissonance, which consists in refuting proposals whose acceptance would entail too great a theoretical and epistemological cost.